Proton Radioactivity Studies - Mahmud, Hassan A A (My University, 2002)
A search for new examples of proton emission from ground and low lying states was conducted at Argonne National Laboratory. Of particular interest were examples of proton emission from nuclei which were deformed or had an odd number of neutrons, the majority of known proton emitters being odd-even and near-spherical. Candidate nuclei were created via fusion evaporation, these recoils then being separated according to their mass to charge ratio by the Fragment Mass Analyser, before being implanted into a Double Sided Silicon Strip Detector. Any subsequent alpha or proton decays were then recorded.
Keywords: nuclear physics; physics